Compressão segmentar do plexo venoso extra-raquidiano: Valor para o diagnóstico de localização das afecções bloqueantes do canal raquidiano - Oswaldo Ricciardi Cruz (Arquivos de Neuro-Psiquiatria)
Outside and inside the vertebral canal, running along its entire length, there is a series of venous plexuses which anastomoses with each other and end in intravertebral veins. They form a real plexuses whose primary disposition is schematically segmental. The plexuses form a series of venous rings at the level of each vertebra. Considering these anatomic data it has been supposed that a strong and lengthened compression at the level of the outside venous plexus will cause a raise in the inside venous pressure which can be detected with a Strauss manometer connected with a needle inserted in the lumbar subarachnoid space. The test would be indicated to locate the lower level of the spinal canal block by the oscilations of the cerebrospinal fluid pressure registered under this level. The test was performed in 5 patients without blocking process in which the Stookey test was normal; in none these cases it was found any raise in the cerebrospinal fluid pressure by local compression of venous plexuses of the spine from cervical untill lumbar vertebrae. The procedure was applied to 5 patients with blocking conditions of the spinal canal, previously diagnosed by the Stookey test. In 4 of these a definite increase (2 to 10 cm.) of the cerebrospinal fluid pressure has been recorded; in these cases the procedure allowed the exact detection of the lower level of the block, later confirmed by myelography and neurosurgery. In one case, however, the test has detected a level that could not be confirmed by myelography or the surgical act.